Rozwój morfologiczny i sprawności specjalnej 13 – letnich chłopców trenujących piłkę nożną w Klubie Sportowym „Pogoń” Łobżenica = Morphological and a special efficiency development 13-years old boys soccer summer training in a sports club "Chase" Łobżenica - Klimczyk, Mariusz; Jagodziński, Krzysztof (Journal of Education, Health and Sport, 2016)
Klimczyk Mariusz, Jagodziński Krzysztof. Rozwój morfologiczny i sprawności specjalnej 13 – letnich chłopców trenujących piłkę nożną w Klubie Sportowym „Pogoń” Łobżenica = Morphological and a special efficiency development 13-years old boys soccer summer training in a sports club "Chase" Łobżenica. Journal of Education, Health and Sport. 2016;6(7):252-265. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57575 http://ojs.ukw.edu.pl/index.php/johs/article/view/3692 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2016. Revised 09.07.2016. Accepted: 09.07.2016. Rozwój morfologiczny i sprawności specjalnej 13 – letnich chłopców trenujących piłkę nożną w Klubie Sportowym „Pogoń” Łobżenica Morphological and a special efficiency development 13-years old boys soccer summer training in a sports club "Chase" Łobżenica Mariusz Klimczyk, Krzysztof Jagodziński Uniwersytet Kazimierza Wielkiego w Bydgoszczy E-mail: Klimczyk1956@poczta.onet.pl Streszczenie Celem pracy było określenie rozwoju morfologicznego i sprawności specjalnej 13 – letnich chłopców trenujących piłkę nożną w KS „Pogoń” Łobżenica. Badana grupa składała się z 17 zawodników, którzy uczęszczali na zajęcia treningowe trzy razy w tygodniu (jednostka treningowa wynosiła 60 minut). Ponadto uczestniczyli cztery razy w tygodniu w zajęciach wychowania fizycznego w szkole. Badania odbyły się w dwóch terminach: pierwszy w sierpniu 2015 roku oraz drugi w kwietniu 2016 roku. Zmierzono masę i wysokość ciała oraz został przeprowadzony „Test sprawności technicznej dla chłopców w wieku 10-14 lat” Jerzego Talagi. Wystąpił progres i duże zróżnicowanie badanych cech. Korelacja między warunkami morfologicznymi, a uzyskanymi punktami w teście sprawności specjalnej ukazała umiarkowaną zależność pomiędzy tymi cechami. Praca wykazuje, że gdy młody zawodnik nie uczęszcza regularnie na treningi, nie notuje progresji swoich umiejętności. Dlatego konieczne jest systematyczne kontrolowanie przez trenera poziomu umiejętności podopiecznych, oraz nanoszenie korekt w planie treningowym by w przyszłości łatwiej wyeliminować to zjawisko. Słowa kluczowe: test, sprawność fizyczna, sprawność specjalna, piłka nożna, rozwój morfologiczny. Abstract The aim of the work was to identify the morphological development and efficiency of a special 13-years old boys soccer summer training in "Chasing" Łobżenica. The test group consisted of 17 players who attended training classes three times a week (training unit was 60 minutes). In addition, participated four times a week in physical education classes in school. The study took place in two periods: the first in August 2015, and the second in April 2016. Measured weight and height of the body and was carried out "technical performance for boys aged 10-14 years old," George Talaga. There was progress and large diversity of subjects. Correlation between morphological features, and obtained points in the test performance special was released to moderate the relationship between these characteristics. The work shows that when the young player does not attend regularly for training, no progression of their skills. It is therefore necessary to systematic monitoring by the skill level of students, and applying adjustments in the training plan to in the future make it easier to eliminate this phenomenon. Keywords: test, physical fitness, the efficiency of the special, football, morphological development.